"Parallels: Constructivism and Artistic 'Isms'" and "'Yes' and 'No' to Constructivism" - Angelov, Valentin (Art in translation, 2025)
"Parallels: Constructivism and Artistic 'isms'" and "'Yes' and 'No' to Constructivism" are sections of Valentin Angelov's book Constructivism in Fine Art and Architecture, published in Sofia in 1972. It focuses on theoretical statements about the place of the art object in the everyday life in the milieus of Constructivism, Bauhaus and Russian constructivism. The author consistently interrogates these trends in terms of: the role of the machine; the autonomy or subordination of artistic integrations to architectural principles; the search for optical effects; the interest in kinetic objects, etc. Valentin Angelov's main thesis is that artistic movements in the West later referred to the ideas and techniques of the left-oriented Constructivists, abandoning "social emotion" and the use of artistic techniques to express subjective attitudes. To argue his thesis convincingly, Angelov arranges the artistic ideas of Constructivism and Pop art in two parallel columns. He articulates the advantages of Constructivism and summarizes: "These ideas also contain praise for human power and reason, and faith in the future: in scientific as well as social progress." However, the author understands well that the horizon of these ideas is utopian: "Of course, all this remained purely in books, but however utopian they may be, these ideas are significant and attractive!" Along with emphasizing the undeniable advantages of Constructivism as thus understood, the art theorist notes that "There are many, many vulnerabilities in the aesthetics and practice of Constructivism." In "'Yes' and 'No' to Constructivism" he strongly distinguishes, according to his understanding, between the productive aspects of the broad trend and those that are unacceptable. Angelov admits, however, that the parallels he draws are intentionally one-sided. He acknowledges the right of existence of artistic experimentation. The nuances of approach and expressions keep the study at a remove from the explicitly ideologized critical writing on Western art during the Cold War and especially in the years of the hardening of censorship after the Prague Spring.